2007
DOI: 10.1681/asn.2006060633
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary Adenylate Cyclase–Activating Polypeptide Stimulates Renin Secretion via Activation of PAC1 Receptors

Abstract: Besides of its functional role in the nervous system, the neuropeptide pituitary adenylate cyclase-activating polypeptide (PACAP) is involved in the regulation of cardiovascular function. Therefore, PACAP is a potent vasodilator in several vascular beds, including the renal vasculature. Because the kidney expresses both PACAP and PACAP-binding sites, it was speculated that PACAP might regulate cardiovascular function by direct vascular effects and indirectly by regulating renin release from the kidneys. PACAP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 29 publications
1
32
0
Order By: Relevance
“…The different PACAP receptors have had specific actions demonstrated in several systems. The PAC1 receptor is important in renin secretion (21) and PACAP-induced depolarizations in superior cervical ganglion neurons (1). The VPAC1 receptor, on the other hand, is necessary for pressureinduced vasodilatation (11), and evidence from our present study suggests that it may be primarily involved in the MAP response observed after intrathecal infusion of PACAP-38.…”
Section: Discussionsupporting
confidence: 48%
“…The different PACAP receptors have had specific actions demonstrated in several systems. The PAC1 receptor is important in renin secretion (21) and PACAP-induced depolarizations in superior cervical ganglion neurons (1). The VPAC1 receptor, on the other hand, is necessary for pressureinduced vasodilatation (11), and evidence from our present study suggests that it may be primarily involved in the MAP response observed after intrathecal infusion of PACAP-38.…”
Section: Discussionsupporting
confidence: 48%
“…It has been suggested that vasopressin release in response to acute dehydration is mediated through activation of PACAP receptors by endogenous PACAP released within the rat supraoptic nucleus (Gillard et al, 2006), and PACAP has been shown to stimulate renin secretion via activation of PAC1-R (Hautmann et al, 2007). These observations show that PACAP plays a role in the regulation of drinking behavior and body fluid balance after water deprivation.…”
Section: Actions Of Pituitary Adenylate Cyclase-activating Polypeptidmentioning
confidence: 73%
“…Plasma renin activity (PRA) is measured as the generation of ANG I without the addition of exogenous renin substrate.] In addition to catecholamines, other hormones, such as the prostaglandins E 2 and I 2 (prostacyclin) (402), dopamine (476), calcitonin gene-related peptide (482), pituitary adenylyl cyclase activating polypeptide (PACAP) (322), and adrenomedullin (397), stimulate the renin release from isolated JG cells and increase the intracellular cAMP concentrations.…”
Section: Campmentioning
confidence: 99%